2009
DOI: 10.1007/s10333-009-0186-6
|View full text |Cite
|
Sign up to set email alerts
|

Fate of phosphate and nitrate in waters of an intensive agricultural area in the dry zone of Sri Lanka

Abstract: The chemistry of surface waters and groundwater draining agricultural catchments in the north-central and northwestern areas of Sri Lanka is described. Hydrochemical data from 296 water samples are used to evaluate water quality and to identify the processes that control nitrate and phosphate concentrations in the water. The results indicate that nutrient concentrations in the groundwaters are greater than those in the surface waters. Increased nutrient levels were observed in groundwater in a selected area in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…However, compared with the higher input of nitrate in to the groundwater low iron content indicates the lower reduction rates of iron in the aquifer due to the higher oxygen content supplied into the highly permeable sand by intense watering. In contrast, reducing condition which is observed in clayey soil areas control the input of nitrate into the groundwater by conversion them into nitrogen and therefore recorded nitrate values show lower figures, although the nitrate fertilizers are applied intensively (Young et al 2010;Gunatilake andGunatilake 2004, Pitawala et al 2007). The measured nitrate concentrations were converted into Nitrate-N values…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, compared with the higher input of nitrate in to the groundwater low iron content indicates the lower reduction rates of iron in the aquifer due to the higher oxygen content supplied into the highly permeable sand by intense watering. In contrast, reducing condition which is observed in clayey soil areas control the input of nitrate into the groundwater by conversion them into nitrogen and therefore recorded nitrate values show lower figures, although the nitrate fertilizers are applied intensively (Young et al 2010;Gunatilake andGunatilake 2004, Pitawala et al 2007). The measured nitrate concentrations were converted into Nitrate-N values…”
Section: Discussionmentioning
confidence: 88%
“…This situation is facilitated by the consecutive cultivations throughout the year. In contrast, seasonal cultivations are carried out in the other areas of the country where the lower nutrient values are recorded (Young et al 2010;Gunatilake and Gunatilake 2004). Steady or even higher fluxes of nitrate can be expected into ground water during rainy season because farmers tend to almost double the fertilizer application during this period to supplement the infiltration losses.…”
Section: Discussionmentioning
confidence: 95%
“…The N and P concentrations in the King Abdullah Canal were higher than the eutrophication level (Alkhoury et al, 2010). An increase in plankton counts was also (Young et al, 2010). The elevated nutrient levels in groundwater could be attributed to fertilizer application.…”
Section: Vulnerability Of Groundwater and Shallow Aquifermentioning
confidence: 88%
“…Surface waters and groundwater draining agricultural catchments in the north-central and northwestern areas of Sri Lanka were collected for nutrient analyses(Young et al, 2010). The elevated nutrient levels in groundwater could be attributed to fertilizer application.The use of swine manure and commercial fertilizer (ammonium nitrate) could also affect leaching of phosphorus to subsurface drain water under a corn-soybean rotation(Hoang et al, 2010) Rozemeijer et al(2010).…”
mentioning
confidence: 99%
“…Irresponsible and excessive application of fertilizer introduce large amounts of nutrients to water bodies; this is especially the case in paddy cultivation (Dissanayake & Weerasooriya, 1987). Young et al (2010) stated that the fertilizer application is high in North Central part of Sri Lanka amounting to six to ten times in excess of the levels recommended by the government. It was clearly observed that intense agricultural practices increase NO 3 ⁻ and PO 4 3 ‾ concentrations as well as other dissolved ions in groundwater (Young et al, 2009;Sutharsiny et al, 2012).…”
Section: Seasonal Variation Of Nitratesmentioning
confidence: 99%